Smoking Cessation Support for Active Smokers - Mulyanti Roberto Muliantino; Yuanita Ananda; Rika Sarfika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Smoking behavior is a significant risk factor causing heart and blood vessel disorders and resulting in high mortality rates. It is essential to stop this behavior as an effort to prevent and control risk factors, break the chain of nicotine addiction, and reduce the prevalence of heart and blood vessel disease. This study aimed to improve the knowledge and attitudes of smoking cessation in active smokers. The coaching clinic using smoking effect video learning for nine active smokers in RT 02 RW 06 Pasar Ambacang, Padang, West Sumatra, Indonesia. A smoking cessation questionnaire was used to measure attitudes of respondents. The results found a significant increase in smoking cessation scores from 18 to 22 after participating in education. Video-based education is effective for increasing knowledge and motivating smokers to want to stop smoking. Continuous education and assistance are needed to increase the implementation of smoking cessation in the community.